The Influence of Work Environment and Work-Life Balance on Turnover Intention Among Generation Z Workers in Gresik Regency - Al Ghifari, Ficho; Swasti, Ika Korika; Evanthi, Ayundha (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the influence of work environment and work-life balance on the likelihood of Generation Z employees in Gresik Regency leaving their jobs. The study employs a quantitative method with a nonprobability sampling technique through purposive sampling, involving 90 Generation Z workers in Gresik Regency. Data were gathered via questionnaire distribution and analyzed using the partial least square method. The study's findings demonstrate that both work environment and work-life balance significantly reduce turnover intention. When Generation Z workers in Gresik Regency perceive their work environment and work-life balance positively, they are less likely to leave their jobs.